Comparison of characteristics of anxiety sensitivity across career stages and its relationship with nursing stress among female nurses in Hunan, China. Issue 5 (4th May 2016) - Li, Shichen; Li, Lingyan; Zhu, Xiongzhao; Wang, Yuping; Zhang, Jinqiang; Zhao, Liping; Li, Lezhi; Yang, Yanjie
Abstract : Objectives: This study aimed to investigate anxiety sensitivity (AS) in female Chinese nurses to better understand its characteristics and relationship with nursing stress based on the following hypotheses: (1) experienced nurses have higher AS than newly admitted nurses; and (2) specific nursing stresses are associated with AS after controlling general stress. Setting: The cross-sectional survey was conducted from May 2014 to June 2015 among female nurses at the provincial and primary care levels in Hunan Province, China. Participants: Among 793 nurses who volunteered to participate, 745 returned and completed the questionnaires. Eligible participants are healthy female nurses aged 18–55 years and exempt from a history of psychiatric disorder or severe somatic disease and/or a family history of psychiatric disorder. Primary and secondary outcome measures: AS was assessed by the Anxiety Sensitivity Index-3 (ASI-3). Anxiety symptoms, general stress and nursing stress were measured by the Beck Anxiety Inventory (BAI), the Perceived Stress Scale (PSS-10) and the Nursing Stress Scale (NSS). Results: There were significant differences overall and in the three dimensions of AS across nurses of different career stages (all p<0.05). Middle and late career nurses had higher AS than early career nurses (all p<0.05), while no significant difference was found between middle and late career nurses. Conflict with physicians and heavy workload had a significant effect on all aspects of AS, whereas lack of support was related to cognitive AS (all p<0.05). Conclusions: After years of exposure to stressful events during nursing, experienced female nurses may become more sensitive to anxiety. Middle career stage might be a critical period for psychological intervention targeting on AS. Hospital administrators should make efforts to reduce nurses' workload and improve their professional status. Meanwhile, more social support and appropriate psychological intervention would be beneficial to nurses with higher AS.